2010
DOI: 10.1038/nature09001
|View full text |Cite
|
Sign up to set email alerts
|

Embolus extravasation is an alternative mechanism for cerebral microvascular recanalization

Abstract: Cerebral microvascular occlusion is a common phenomenon throughout life1,2 that could be an underappreciated mechanism of brain pathology. Failure to promptly recanalize microvessels may lead to disruption of brain circuits and significant functional deficits3. Hemodynamic forces and the fibrinolytic system4 are considered the principal mechanisms responsible for recanalization of occluded cerebral capillaries and terminal arterioles. However, using high resolution fixed tissue microscopy and two photon imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 29 publications
5
159
2
1
Order By: Relevance
“…However, based on the previous research, we have learned the following: (1) a presumable inverse relationship exists between the size and number of the disrupted clots required to create cerebral ischemia and infarction, 22 (2) most distal protection devices for carotid stenting have a pore size between 100 and 200 µm, suggesting particles with size <100 to 200 µm are less likely to result in severe embolic stroke, 23,24 and (3) other than the fibrinolytic system and hemodynamic forces, recanalization of cerebral microvascular occlusion could be achieved by embolus extravasation. 25,26 As documented in a recent clinical report, 27 among all the clot debris, a small fraction were larger fragments with size between 200 and 1600 μm. The number of these particles was significantly less than that of the small debris; however, they are thought to lead to significant cerebral occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the previous research, we have learned the following: (1) a presumable inverse relationship exists between the size and number of the disrupted clots required to create cerebral ischemia and infarction, 22 (2) most distal protection devices for carotid stenting have a pore size between 100 and 200 µm, suggesting particles with size <100 to 200 µm are less likely to result in severe embolic stroke, 23,24 and (3) other than the fibrinolytic system and hemodynamic forces, recanalization of cerebral microvascular occlusion could be achieved by embolus extravasation. 25,26 As documented in a recent clinical report, 27 among all the clot debris, a small fraction were larger fragments with size between 200 and 1600 μm. The number of these particles was significantly less than that of the small debris; however, they are thought to lead to significant cerebral occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…An elegant study has recently shown that part of the microemboli (8 to 20 mm) are cleared from microcirculation within 2 hours after their infusion into the carotid artery in mice. 85 Yet, a substantial number of emboli are retained in the microvasculature and interrupt the blood flow. Obstructed microvessel lumina reopen after extravasation of the clot to the perivascular area within the following days.…”
Section: Can We Improve the Stroke Outcome After Thrombolysis?mentioning
confidence: 99%
“…16 Envelopment of emboli by endothelial membrane projections followed by expulsion into perivascular parenchyma was detected after a few days. This process may be a critical endogenous mechanism through which reestablishment of perfusion occurs after occlusion of cerebral microvessels.…”
Section: In Vivo Imaging Of Neurovascular Remodeling After Strokementioning
confidence: 99%